Efficient Low Voltage Amplification Using Self Starting Voltage Regulator For Storage System - Mohd Nasir, Haslinah; Mohamed Aminuddin, Mai Mariam (Engg Journals Publications, 2014)
This paper presents a storage system design based on energy harvesting to achieve battery-less for Wireless Sensor Network (WSN) application. The storage system is part of the Wireless Sensor Energy Harvesting to store and amplify the energy harvested from the surroundings. The proposed method must be consumes very little power and suitable for ambient environmental sources such as vibration, wind and RF energy and be able to boost up the energy for storage system. The output of the harvested voltage is insufficient for most applications, therefore the system will boost up the input voltage level using DC to DC converter topology to higher dc voltage. The DC to DC converter shall be designed to suit the types of storage required. The output voltage of this DC converter should be sufficient to charge either capacitor or supercapacitor that will be use in this system as the energy storage system. The supercapacitor will provide power to energize any system such as in this case wireless sensor network [1]. In the case of wireless sensor network for example, the node would require the energy during transmitting and receiving data only whereas during standby mode or sleep mode, the amount of energy required would be very small [2]. Therefore the storage system will make use of this standby time or sleep mode of the sensor node to store as much energy as possible. The presented DC to DC converter in this paper has high efficiency upto 85.4% with input voltage between range 300mV to 600mV.